Experiences of Mothers of Multiple Children with Autism Spectrum Disorder: An Interpretative Phenomenological Analysis Study - Hatice Şengül Erdem (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: This study aimed to investigate the experiences of mothers of multiple children with autism spectrum disorder (ASD).Method: Nine mothers of multiple children with ASD participated in the research, designed as an interpretative phenomenological analysis study, and data were collected through semi-structured interviews. In the data analysis, the interpretative phenomenological analysis method was employed to reveal the mothers’ personal statements and emotional reflections in depth.Findings: As a result of the analysis, three main themes were reached, the center of life: Being a mother of two children with autism, gradually increasing isolation, and empowerment attempts. In line with the findings, mothers continue their lives by putting their children with ASD at the center, and they become increasingly lonely in social life. Mothers experience difficulty in maintaining their daily lives, have intense worries about the future, think that they lack the support resources they need, and feel that having multiple children with ASD causes transformations in their relationships with their spouses and their social networks, which will increase their loneliness. Furthermore, mothers develop various strategies to empower themselves. These strategies have emerged as religious beliefs, comparing their children with each other or with children with more severe disabilities, and focusing on the minor achievements of their children.Discussion: There are few studies on the subject, and the experiences of mothers of multiple children with ASD are similar to the findings of research investigating the experiences of mothers of multiple children with disabilities or mothers of a child with ASD.Conclusion and Recommendations: Whereas mothers of multiple children with ASD experience intense social isolation and put the “motherhood role” at the center of their lives, on the one side, they feel obliged to empower themselves and develop some strategies to this end, on the other side. According to the study findings, it is suggested that arrangements are needed to facilitate the lives of mothers of multiple children with ASD and the experiences of mothers should be examined with studies to be performed with a larger number of participants.